A rapid method for isolation of total DNA from pathogenic filamentous plant fungi - González Mendoza, D.; Argumedo Delira, Rosalba; Morales Trejo, A.; Pulido Herrera, A.; Cervantes Daz, L.; Grimaldo Juarez, O.; Alarcón, Alejandro (2010)
DNA isolation from some fungal organisms of agronomic importance is difficult because they have cell walls or capsules that are relatively unsusceptible to lysis. We have developed a fast DNA isolation protocol for Fusarium oxysporum, which causes fusarium wilt disease in more than 100 plant species, and for Pyrenochaeta terrestris, which causes pink root in onions. This protocol was based on the sodium dodecyl sulfate/ phenol method, without β-mercaptoethanol and without maceration in liquid nitrogen; it uses phenol/chloroform extraction to remove proteins and co-precipitated polysaccharides. The A260/280 absorbance ratios of isolated DNA were around 1.9, suggesting that the DNA fraction was pure and may be used for further analysis. Additionally, the A260/230 values were higher than 1.8, suggesting negligible contamination by polysaccharides. The DNA isolated by this protocol is of sufficient quality for molecular applications; this technique could be applied to other organisms that have similar substances that hinder DNA extraction.